KONSEP TRI HITA KARANA PADA LOGO YAYASAN DHARMA SENI MUSEUM NEKA DI UBUD - Ayu Widiari Widyaswari (Jurnal Nawala Visual, 2019)
In a media, has a concept in its design. A concept will later become a trait or identity in a work or media. The concept is an idea that represents a form that can give birth to perceptions of an object in simple or abstract form. In this study, will discuss the concept of a logo, namely the logo of the Neka Museum Art Foundation located on Ubud, Sanggingan Street, Gianyar. At the Museum Neka Foundation logo, the concept used is the concept of Tri Hita Karana. The method that will be use in research is the observation method conducted at the research location, namely at the Neka Museum, the interview method is by structurally interviewing the designer of the Neka Museum Foundation logo about the concept of the logo, and the library method relating to design theories visual communication such as concepts, logos, and Tri Hita Karana theory itself. The concept Tri Hita Karana in the logo of the Museum Neka Foundation is elaborated from each of the existing design elements, all of which have meaning.